Cancer‐linked genetic testing: The key role of cultural influences: In this second of a two‐part series, genetic testing for hereditary cancers is promising more targeted approaches to prevention and intervention, but cultural differences in perceptions of utility, autonomy, and decision‐making loom large in determining whether and how such testing is conducted. Issue 1 (2nd January 2023) - Nelson, Bryn; Faquin, William
Abstract : This news section is written by a medical journalist and offers Cancer Cytopathology readers timely information on events, issues, and personalities of interest to the subspecialty. In this second of a two‐part series, genetic testing for hereditary cancers promises more targeted approaches to prevention and intervention, but cultural differences in perceptions of utility, autonomy, and decision‐making have a major impact on how such testing is conducted.